PENGARUH PROFITABILITAS, LIKUIDITAS, EFISIENSI, NET INTEREST MARGIN DAN NON PERFORMING LOANTERHADAP CAPITAL ADEQUACY RATIO PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2012-2016 - Wahyu Kurniawan Suryo Sularso, 12.05.52.0092; Anggana Lisiantara, Gregorius (Students' Journal of Accounting and Banking, 2018)
This study aims to examine the effect of profitability, liquidity, efficiency, Net Interest Margin and Non Performing Loan against Capital Adequacy Ratio in banking companies listed on Indonesia Stock Exchange Period 2012-2016, this study entitled "The Effect of Profitability, Liquidity, Efficiency, Net Interest Margin and Non Performing Loan Against Capital Adequacy Ratio in banking companies listed on Indonesia Stock Exchange (IDX) period 2012 to 2016". Population in this study all listed banking companies (Go Public) in Indonesia Stock Exchange (BEI) period 2012-2016. Sampling method with judgment sampling method is one of the purposive sampling by taking samples that have been determined previously based on the intent and purpose of the study. The provisions of samples taken are as follows: Banking companies include financial statements of 2012 - 2016 and Reports included in the form of complete data obtained a sample of 90data sample. Data used secondary data with data analysis using liner regression. The results of research as follows Return On Assets negatively affect the Capital Adequacy Ratio until hypothesis the first to push away. Loan to Deposit Ratio has a positive influence on Capital Adequacy Ratio until hypothesis the second to push away. Efficiency negatively affects the Capital Adequacy Ratio until hypothesis the third to acceptance. Net Interest Margin positively affects the Capital Adequacy Ratio until hypothesis the fourth to acceptance. Non Performing Loan has a positive effect on Capital Adequacy Ratiountil hypothesis the five to push away. Keywords: Return On Assets, Loan to Deposit Ratio, Efficiency, Net Interest Margin, Non Performing Loan and Capital Adequacy Ratio.